2015
DOI: 10.1002/jcb.25129
|View full text |Cite
|
Sign up to set email alerts
|

Gene Signatures of 1,25‐Dihydroxyvitamin D3 Exposure in Normal and Transformed Mammary Cells

Abstract: To elucidate potential mediators of vitamin D receptor (VDR) action in breast cancer, we profiled the genomic effects of its ligand 1,25-dihydroxyvitamin D3 (1,25D) in cells derived from normal mammary tissue and breast cancer. In non-transformed hTERT-HME cells, 483 1,25D responsive entities in 42 pathways were identified, whereas in MCF7 breast cancer cells, 249 1,25D responsive entities in 31 pathways were identified. Only 21 annotated genes were commonly altered by 1,25D in both MCF7 and hTERT-HME cells. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 52 publications
2
25
1
Order By: Relevance
“…Although RAS transformation inhibits 1,25(OH) 2 D action by phosphorylation of the VDR heterodimeric partner RXRα in prostate epithelial cells and keratinocytes (10,34,36) , our new data suggest that the primary mechanism for RAS-mediated inhibition of 1,25(OH) 2 D action in intestinal cells is due to a 70% reduction of VDR gene expression. This is consistent with other groups that have reported that Ras-activating mutations reduce VDR mRNA and/or protein levels in NIH3T3 cells (H-Ras (37) ), non-small cell lung cancer cell lines (K-Ras (12) , and mouse mammary epithelial cells (H-Ras (11,32) ). Thus, VDR loss may be a critical contributor to Ras-mediated transformation and VDR loss may reduce the beneficial effects of high vitamin D status on cancer progression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although RAS transformation inhibits 1,25(OH) 2 D action by phosphorylation of the VDR heterodimeric partner RXRα in prostate epithelial cells and keratinocytes (10,34,36) , our new data suggest that the primary mechanism for RAS-mediated inhibition of 1,25(OH) 2 D action in intestinal cells is due to a 70% reduction of VDR gene expression. This is consistent with other groups that have reported that Ras-activating mutations reduce VDR mRNA and/or protein levels in NIH3T3 cells (H-Ras (37) ), non-small cell lung cancer cell lines (K-Ras (12) , and mouse mammary epithelial cells (H-Ras (11,32) ). Thus, VDR loss may be a critical contributor to Ras-mediated transformation and VDR loss may reduce the beneficial effects of high vitamin D status on cancer progression.…”
Section: Discussionsupporting
confidence: 93%
“…For example, others have found that VDR mRNA or protein levels are reduced in human colon tumors (7,28) and other cancers (2931) . Forty percent of colon tumors have mutations in the K-RAS gene (9) and previous research has shown that RAS activating mutations suppress 1,25(OH) 2 D action in some cells (1012,3234) but enhance 1,25(OH) 2 D action in MG-63, HeLa, and COS-1 kidney cells (33,35) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent whole genome profiling on cells derived from normal mammary tissue and breast cancer reveals the regulation of a set of immune genes by 1,25(OH) 2 D 3 . Among these genes, soluble CD14b, which may contribute to the protection against breast cancer, seems to be consistently induced by 1,25(OH) 2 D 3 (412). Induction of CD14 by 1,25(OH) 2 D 3 is confirmed by a microarray study on fresh tumor slices exposed to 1,25(OH) 2 D 3 (311).…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 72%
“…Intriguingly, these results are indicative of a role of the VDR as an enhancer of cell proliferation (96). Microarray profiling of nontumorigenic mammary epithelial cells after treatment with 1,25(OH) 2 D 3 revealed the regulation of a whole set of metabolic genes such as SLC1A1 and GLUL by 1,25(OH) 2 D 3 (412). SLCA1 encodes a plasma membrane glutamate transporter that is induced by 1,25(OH) 2 D 3 , whereas GLUL, which encodes glutamine synthetase, is repressed by 1,25(OH) 2 D 3 .…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 94%
“…Interestingly, the induction of SLC1A1 by 1,25D observed in hTERT-HME1, HME and DCIS.com cells was abrogated in MCF10A cells (which have MYC amplification) and in breast cancer cells MCF7 and Hs578T (10). In addition, induction of SLC1A1 gene expression by 1,25D was blunted in HME cells expressing SV-40 (HME-LT cells) and those expressing SV-40 plus oncogenic RAS (HME-PR cells) (11). These studies suggest that 1,25D enhances SLC1A1 expression in normal mammary epithelial cells but that expression of this gene and its regulation by 1,25D is often abrogated in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%